The cross-section of expected stock returns in the property/liability insurance industry - Ben Ammar, Semir; Eling, Martin; Milidonis, Andreas (Journal of Banking & Finance, 2018)
We conduct a comprehensive asset pricing analysis for the U.S. property/liability insurance industry using monthly data from 1988 to 2015. We find that state-of-the-art models such as the Fama and French (2015) five-factor model cannot explain the returns of property/liability insurance stocks in a satisfactory way. We adapt the model proposed by Adrian et al. (2015) for financial institutions and define an insurance-specific five-factor asset pricing model (INS5), which can explain the cross-section of property/liability insurance-stock returns better than competing models. The priced factors are the market return, the book-to-market ratio, return on equity, short-term reversal, and the spread between the property/liability insurance sector and the market return.